EARLY EXPERIENCE OF PNEUMATIC LITHOCLAST FOR THE MANAGEMENT OF URETERIC STONES AT PESHAWAR - Nawaz, Ahmad; Wazir, Bakhtawar Gul; Orakzai, Akhtar Nawaz (Journal of Ayub Medical College Abbottabad, 2016)
Background: Pakistan lies in the Afro-Asia stone belt. Ureteric calculi are common occurrence and a major burden on health care facilities in Pakistan. The objective of this study was to assess the efficacy and safety of pneumatic lithoclast in the management of ureteric calculi. Methods: Case series study Department of Urology at Institute of Kidney Diseases Hayatabad Peshawar, from 1st Oct 2010 to 1st Oct 2011. One-hundred adult patients with ureteric calculi ‰¥ 0.7 cm were evaluated by history, physical examination, routine blood and urine examination after taking their written informed consent and approval of ethical committee. Ultrasound and X-ray KUB were done with IVU if required. All patients underwent ureteroscopy within intracorporeal lithotripsy and JJ stenting. Patients were followed up with post-op X-ray KUB at 24 hours and then weekly intervals till they became stone free. Following parameters were assessed: stone size, site, laterality, degree of fragmentation, success rate, stone migration and complications. Inability to reach the calculus with URS, proximal migration of stone or requirement of another/auxiliary procedure was considered failure. Results: One hundred and ten patients were enrolled with a mean age of 38±10 years. There were 72 males and 28 females. Fifty-eight calculi were on right and 42 on left side. 24, 24 and 52 stones were in upper, middle and lower ureter respectively. Forty stones measured 7-10 mm, 52 measured 11-15 mm and 8 measured 16-20 mm in size. 98 stones were broken while 2 calculi migrated proximally. Overall success rate was 90% (Efficiency Quotient =78.95). Success rate in upper, middle and lower ureter was 83.3%, 83.3% and 96.1% respectively. 10 and 2 patients required ESWL and open ureterolithotomy, respectively, as additional treatment. Mean operative time was 33.5 minutes. There were no major complications. Conclusions: Pneumatic lithoclast with URS is effective and safe in the management of the ureteric calculi with some limitations in the upper ureter. Keywords: Ureteric stones; Ureterorenoscopy; Pneumatic Lithoclast